Apathy in Alzheimer's disease and frontotemporal dementia: Distinct clinical profiles and neural correlates. (June 2018) - Kumfor, Fiona; Zhen, Alice; Hodges, John R.; Piguet, Olivier; Irish, Muireann
Abstract: Objective: Apathy is the most prevalent and disabling non-cognitive symptom of dementia and affects 90% of patients across the disease course. Despite its pervasiveness, how apathy manifests across dementia syndromes and the neurobiological mechanisms driving these symptoms are poorly understood. Here, we applied the multidimensional ABC model of apathy, which recognizes Affective, Behavioural and Cognitive apathy, in Alzheimer's disease (AD) and behavioural-variant frontotemporal dementia (bvFTD). Methods: One hundred and twenty-two patients (53 AD; 69 bvFTD) were included. Informants completed the Neuropsychiatric Inventory (NPI), Cambridge Behavioral Inventory and Disability and Dementia scale to quantify Affective, Behavioural and Cognitive apathy. All patients underwent structural magnetic resonance imaging (MRI) and voxel-based morphometry (VBM) was employed to identify brain regions correlated with increased Affective, Behavioural and Cognitive apathy. Results: On the NPI, 60% of AD and 84% of bvFTD patients had some degree of apathy, but bvFTD had more severe and more frequent symptoms than AD. Importantly, bvFTD patients had higher affective and cognitive apathy whereas AD had higher cognitive apathy only. Neuroimaging analyses revealed that affective apathy was associated with the ventral prefrontal cortex; behavioural apathy with the basal ganglia; and cognitive apathy with the dorsomedial prefrontal cortex. Finally, affective and behavioural apathy significantly predicted carer burden. Conclusions: Our results support the notion that apathy is multidimensional and manifests differently across dementia syndromes. Thus, novel interventions which target these divergent mechanisms will be necessary to improve motivation and goal-directed behaviour in people with dementia.